LIVE FORENSICS ACQUISITION FILE SHARING SAMBA PADA MIKROTIK ROUTER OS - Abdul Rohman Supriyono; Yudi Prayudi (Fakultas Sains dan Teknologi UIN Sunan Kalijaga Yogyakarta, 2018)
Smart Router is a router device that is equipped with Smart Wi-Fi software that allows us to easily manage and monitor the home network, and has more features or services than regular routers in general. Routers of this type include one solution in building a local area network that can be used as file server in file sharing. But regardless of the benefits it does not rule out the possibility of a crime by utilizing file sharing. Therefore, in the field of digital forensics required live forensic methods and live acquisitions, since the smart router belongs to a critical electronic item category, where data (log) can be lost when the device is turned off.